Host-specificity of Monoxenous Trypanosomatids: Statistical Analysis of the Distribution and Transmission Patterns of the Parasites from Neotropical Heteroptera - Kozminsky, Eugene; Kraeva, Natalya; Ishemgulova, Aygul; Dobáková, Eva; Lukeš, Julius; Kment, Petr; Yurchenko, Vyacheslav; Votýpka, Jan; Maslov, Dmitri A (Protist, 2015)
Host-parasite relationships and parasite biodiversity have been the center of attention for many years; however the primary data obtained from large-scale studies remain scarce. Our long term investigations of trypanosomatid (Euglenozoa: Kinetoplastea) biodiversity from Neotropical Heteroptera have yielded almost one hundred typing units (TU) of trypanosomatids from one hundred twenty host species. Half of the parasites' TUs were documented in a single host species only but the rest were found parasitizing two to nine species of hosts, with logarithmic distribution best describing the observed distribution of parasites among hosts. Different host superfamilies did not show significant differences in numbers of trypanosomatid TUs they carry, with exception of Pyrrhocoroidea which showed higher parasite richness than any other group tested. Predatory reduviids shared significantly larger numbers of parasite TUs with phytophagous mirids and coreids than the numbers shared between any other groups. These results show that the specificity of trypanosomatid-heteropteran associations is not very strict: parasites seem to be transmissible between different host groups within the same niche and predatory hosts may acquire parasites from their prey.
Keywords: Biodiversity; host-parasite specificity; Trypanosomatids; Genes, Protozoan; Host-Parasite Interactions; fylogeneze; interakce hostitele a parazita; biodiversity; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; biodiverzita; molekulární sekvence - údaje; Spliced Leader RNA.; RNA, Protozoan; hostitelská specificita; protozoální geny; Trypanosomatina; Animals; RNA, Spliced Leader; RNA se sestřihovou vedoucí sekvencí; zvířata; RNA protozoální; Molecular Sequence Data; Heteroptera; Host Specificity